High intensity ultrasound-assisted extraction of medicinal blue dye from the bark of jatropha curcas - Prasad, Reddy (2011)
Extraction and product recovery are the most crucial steps in evaluation of valuable active compounds from various plant parts. In this study, extraction of gallic acid from Jatropha curcas stem bark was investigated using different techniques of extraction. The aims of this study were to optimize the extraction parameters as well as to do mathematical modeling of the extraction process. The work can be divided in five main stages namely as sample preparations, extraction studies, extraction analysis, parameters optimization and modeling. In sample preparations, the bark was stripped from the branches, cut into small pieces and dried in an oven. The samples were then grounded and sieved to obtain sample size of approximately 1 mm. Four extraction techniques were employed such as shake flask extraction, Soxhlet extraction, ultrasonic-assisted extraction (UAE) and microwave-assisted extraction (MAE). Temperature, solvent composition, time and power for UAE and MAE were the extraction parameters used in the extraction studies. The extracts were further undergone analysis process. Total phenolic content (fPC) determined the amount of phenolic compounds in the extracts. Quantification of gallic acid in the extracts was done using high performance liquid chromatography (HPLC). In optimization part, response surface methodology (RSM) was employed to optimize the extraction parameters. UAE gave the best results among all the extraction techniques. The optimal conditions for UAE were: employing 50% ethanol as solvent, time 30 min, temperature 40°C and power 76.68 Watt. The extraction efficiency increased in the following order: shake flask< Soxhlet< MAE< UAE.